Case report: A novel mosaic nonsense mutation of PCDH19 in a Chinese male with febrile epilepsy - Chen, Guilan; Zhou, Hang; Lu, Yan; Wang, You; Li, Yingsi; Xue, Jiaxin; Cheng, Ken; Huang, Ruibin; Han, Jin (Frontiers in Neurology, 2022)
The clinical features of PCDH19 gene mutation include febrile epilepsy ranging from mild to severe, with or without intellectual disability, cognitive impairment, and psych-behavioral disorders, but there was only a few research on males with the mosaic mutation of PCDH19. This study reported a novel, de novo and mosaic PCDH19 nonsense mutation (NM_001184880: c.840C>A, p. Tyr280*) a Chinese male in early middle childhood by trio whole-exome sequence (Trio-WES) and confirmed by Sanger sequence. The proportion of mosaic mutation (c.840C>A, p. Tyr280*) in PCDH19 was 27.9% in, buccal mucosal cells, 48.3% in exfoliated cells in urine and 42.4% in peripheral blood of proband. He had the first onset of seizures in toddlerhood with febrile epilepsy, mild impaired cognitive psychological, and behavioral abnormalities. The electroencephalography (EEG) exhibited sharp waves and sharp slow complex waves in the bilateral parietal, occipital, and posterior temporal regions during the interictal period. By cranial magnetic resonance imaging (MRI), punctate white matter lesions appeared in the periventricular white matter and slightly plump bilateral ventricles. He gained a good control of epilepsy with depakine and Keppra. This study might expand the genotypes and broaden the spectrums, as well as contribute to understanding the mechanism and treatment of PCDH19-related encephalopathy.